Oculomotor response in male collegiate pole vaulters after repeated head impact due to falls from heights: a pilot longitudinal study - Taisei Hakozaki; Shota Enoki; Seiya Sakihama; Soju Ishimatsu; Rieko Kuramochi (Japanese Society of Physical Fitness and Sports Medicine, 2021)
Subconcussive head impact exposure in sports is a complex public health issue. Although many head impacts are asymptomatic, the near point of convergence (NPC) that measures the closest point of focus before diplopia occurs, has been shown to reflect subclinical neuronal damage. Studies have not been conducted on the effect of repeated head impact exposure due to falls from heights, like in pole vaulting. This study examines the NPC response in collegiate pole vaulters with indirect head impact history due to falls from heights. This prospective observational study included four-pole vaulters and three decathletes. The study was conducted during the end of the Japanese collegiate track and field season. The measurements were taken at pre-practice, 0 h post-practice, 24 h post-practice, 1 week post-practice, 2 weeks post-practice, 3 weeks post-practice, and 4 weeks post-practice. Players completed the NPC test and the symptom checklist. There was a significant difference in the NPC value at pre-practice and 4 weeks post-practice; P = 0.048. Compared to pre-practice values, NPC significantly increased at 0 h post-practice (mean [SE] values: pre-practice, 5.61 [0.69] cm; 0 h post-practice, 7.31 [0.79] cm; P = 0.02). At 3 weeks post-practice and 4 weeks post-practice, NPC values were significantly reduced compared to the values at 0 h post-practice (mean [SE] values: 0 h post-practice, 7.31 [0.79] cm; 3 weeks post-practice, 5.75 [0.61] cm; 4 weeks post-practice, 5.52 [0.64] cm). This study reveals that NPC can be impaired by pole vaulting. The increased NPC returned to normal after 3 - 4 weeks of rest.